Analisis Karakter Disiplin Siswa dalam Ekstrakurikuler Drum Band di Sekolah Dasar - Muhammad Rizky Syifaurrahmat; Irna Khaleda Nurmeta; Luthfi Hamdani Maula (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Discipline is the key to success in various aspects of life. This research aims to analyze the discipline character of students in extracurricular drum band in elementary schools. This research focuses on two aspects of discipline, namely time discipline and action discipline. This research was carried out on drum band extracurricular activities at SDN Pakujajar CBM Kota Sukabumi. The research uses qualitative methods, data is collected through observation, interviews and documentation. The research results show that students who are members of the extracurricular drum band have a disciplined character. The character of this discipline includes discipline towards time and discipline towards actions. Time discipline is reflected in arriving on time and being able to make the best use of time. Discipline in actions is shown through obedience to rules, being orderly, being responsible for one's equipment, respecting each other and being serious when training. Disciplined character is created because of habits. With this, research shows that extracurricular drum band in elementary schools plays a role in forming disciplinary character. The drum band extracurricular can be a means of cultivating disciplined character that is useful in preparing students to face the outside world.